Child outcomes after prenatal exposure to platinum and taxane-based chemotherapy: an unplanned interim analysis of the international network on cancer, infertility, and pregnancy studyResearch in context - Indra A. Van Assche; Kristel Van Calsteren; Evangeline A. Huis in ’t Veld; Mathilde van Gerwen; Laura Heylen; Charlotte L. LeJeune; Elyce Cardonick; Michael J. Halaska; Robert Fruscio; Monica Fumagalli; Elisabeth M. van Dijk-Lokkart; Jurgen Lemiere; et al. (EClinicalMedicine)
Summary: Background: Platina and taxanes are frequently used chemotherapeutic agents to treat cancer, also when diagnosed during pregnancy. This report presents an interim analysis of the largest series of children prenatally exposed to platinum and/or taxane agents and aims to determine their physical health and neurocognitive outcomes. Methods: As part of a multicentre, prospective cohort study (ClinicalTrials.gov: NCT00330447), children born between 2000 and 2022 were assessed between 2005 and 2024 at ages 1.5–18 years (interim analysis; median length of follow-up, 3.2 years (IQR 3.0–6.4)) by a comprehensive neurocognitive test battery, parent-reported questionnaires, and a physical assessment. Mixed-effects regression and Type III Analysis of Variance models were used to investigate associations between these outcomes and platinum/taxane cumulative dose and agent type, with best-fit models corrected for age and covariates (gestational age at birth, chemotherapy timing, other chemotherapy, sex, parental education level, maternal death). Findings: In total, 144 children were included (13% exposed to platinum, 62% to taxanes, 25% to both). Of these, 101 were assessed at age 1.5 years, 96 at age 3, 63 at age 6, 32 at age 9, 18 at age 12, 7 at age 15, and 2 at age 18 years. Neurocognitive outcomes were within normal ranges across all ages, compared with test-specific normative data. Eight children (6%) reported ototoxicity, seven (5%) reported chronic medical conditions, three (2%) had congenital malformations, and two (1%) were diagnosed with Attention-Deficit Hyperactivity Disorder. Thirty-three children (23%) needed extra neurocognitive support, of which 64% were born preterm. Children prenatally exposed to paclitaxel scored lower on visuospatial (β = 0.64 ± 0.21, p = 0.0052) and verbal memory (β = 0.68 ± 0.27, p = 0.015) than those exposed to docetaxel. Interpretation: In this interim analysis, we found normal neurocognitive outcomes and no increase in congenital malformations nor medical conditions after prenatal exposure to platinum/taxane-based chemotherapy. However, owed to the limited number of older children, further investigation regarding their potential neurotoxicity and its long term effects is necessary in follow-up studies with larger samples. Funding: Kom Op Tegen Kanker, KWF Kankerbestrijding, Stichting Tegen Kanker, Cooperatio program, Research Foundation Flanders.